2021
DOI: 10.3390/cancers13235984
|View full text |Cite
|
Sign up to set email alerts
|

Organ Specific Copy Number Variations in Visceral Metastases of Human Melanoma

Abstract: Malignant melanoma is one of the most aggressive skin cancers with high potential of visceral dissemination. Since the information about melanoma genomics is mainly based on primary tumors and lymphatic or skin metastases, an autopsy-based visceral metastasis biobank was established. We used copy number variation arrays (N = 38 samples) to reveal organ specific alterations. Results were partly completed by proteomic analysis. A significant increase of high-copy number gains was found in an organ-specific manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…(unpublished data) Meanwhile, in most of these cases, CNV was not demonstrated to be responsible for such an ectopic expression; therefore, epigenetic mechanisms must be considered as a driving factor. In a recent study addressing human melanoma metastases, genome-wide CNV analysis revealed copy number gain of several CD genes including new ones: CD1a/e, CD48, CD84, CD93, CD209, CD217, and CD247, as well as known ones such as CD36, CD40, CD47, CD70, CD160, CD172, CD320, and IDO1 [96]. In all those instances, mRNA and protein expressions have been validated in an independent dataset.…”
Section: Novel Form Of Cancer Plasticity: Immunogenic Mimicrymentioning
confidence: 87%
See 2 more Smart Citations
“…(unpublished data) Meanwhile, in most of these cases, CNV was not demonstrated to be responsible for such an ectopic expression; therefore, epigenetic mechanisms must be considered as a driving factor. In a recent study addressing human melanoma metastases, genome-wide CNV analysis revealed copy number gain of several CD genes including new ones: CD1a/e, CD48, CD84, CD93, CD209, CD217, and CD247, as well as known ones such as CD36, CD40, CD47, CD70, CD160, CD172, CD320, and IDO1 [96]. In all those instances, mRNA and protein expressions have been validated in an independent dataset.…”
Section: Novel Form Of Cancer Plasticity: Immunogenic Mimicrymentioning
confidence: 87%
“…In all those instances, mRNA and protein expressions have been validated in an independent dataset. It is of note that the majority of these CD gene amplifications were detected in lung metastases, to a lesser extent in liver ones, and rarely observed in brain metastases, suggesting a unique clonal selection [96]. The pertinent literature on ectopic immune cell gene expressions in cancer is summarized on Table 1.…”
Section: Novel Form Of Cancer Plasticity: Immunogenic Mimicrymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in melanoma, as in most solid tumors, hypoxia is associated with aggressiveness and metastases ( Kalaora et al 2022 ). The fraction of genome altered is the percentage of genome that has been affected by copy number gains or losses, and it has recently been shown that, in melanoma, it increases in visceral metastases compared with their respective primary tumors ( Papp et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The typical characteristics of cutaneous melanoma are early dissemination and subsequent metastatic colonization of multiple organs, for instance, lymph nodes, lung, liver, bone, and brain are common metastatic sites of skin melanoma (3). It's worth noting that metastatic melanoma is the main cause of its high mortality and among multiple organs that may be colonized by cutaneous melanoma, the lung is one of the most common distant metastatic sites of melanoma (3)(4)(5)(6). The incidence of pulmonary metastasis of melanoma accounts for 5% of all malignant metastases, and the mortality rate of pulmonary metastasis of melanoma is also very high (7).…”
Section: Introductionmentioning
confidence: 99%